Communicative and pragmatic skills: down syndrome vs williams syndrome - Esther Moraleda-Sepúlveda; Patricia López-Resa; Noelia Pulido-García; Paula López-Peces; Noelia Santos-Muriel; Gabriela Gutierrez-Arce (Global Journal of Rare Diseases - Peertechz Publications, 2022)
Down Syndrome (DS, hereinafter) is a chromosomal alteration produced by changes in the DNA sequence of chromosome 21, in addition to being the main cause of intellectual disability in the world [1]. According to the World Health Organization [2], DS has a worldwide prevalence of 1 in every 1,000 live births, but these figures vary due to different factors such as prenatal diagnosis. Others say that DS occurs in about 1 in 700 births [3].